خصائص اللغة العربية - Elok Rufaiqoh (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2022)
مستخلص البحث أهداف هذا البحث هي وصف خصائص اللغة العربية من ناحية أصواتها، و اشتقاقها، و إعرابها، وترادفها، و سهولتها. ونوع هذا البحث هو البحث المكتبي. والمنهج المستخدم هو المنهج الوصفي التحليلي. وهو يحاول أن يحلل خصائص اللغة العربية من الجهة المعيارية ومن جهة أخرى. ويهتم هذا المنهج بوصف النصوص اللغوية وصفا واقعيا للنصوص. ونتائج البحث هي أن اللغة العربية خصائص التي تُميِّزها باللغة الأخرى سواء من حيث صوتها، و صرفها، ونحوها، وغير ذلك. Abstract The objectives of this research are to describe the characteristics of the Arabic language in terms of its sounds, derivation, syntax, synonymy, and ease. The type of this research is desk research. The method used is the descriptive analytical method. It tries to analyze the characteristics of the Arabic language from the normative side and from the other side. This approach is concerned with describing linguistic texts as a realistic description of the texts. The results of the research are that the Arabic language has characteristics that distinguish it from the other language, whether in terms of its sound, its morphology, grammar, and so on.